Digitalization of Marriage Dispensation Assistance: Innovating Judicial Deliberation Under Supreme Court Regulation 5/2019 - Fadhli, Ashabul; Warman, Arifki Budia; Rahmi, Fathur (Al-'Adl, 2026)
This study examines the optimization of the Family Learning Center (PUSPAGA) in Bukittinggi City in assistance marriage dispensation applicants, as mandated by Supreme Court Regulation (PERMA) No. 5 of 2019. There is a prevailing tendency for recommendation letters submitted by applicants to Religious Courts are still at the formality level, without ensuring whether the mentoring process has actually been carried out substantially. This condition will become even more complicated when it is found that the applicant cannot attend regular assistance due to geographical conditions. This qualitative study, utilizing a socio-legal (juridical-empirical) approach, performs an in-depth case study on the electronic assistance process in Case Number 400.113/DP3APPKB-PHA/2025. Data were gathered through semi-structured interviews with PUSPAGA counselors and observations regarding the effectiveness of electronic media as a assistance instrument. The findings reveal that the utilization of electronic media—prompted by the applicants' geographical problems— meets the standards of Article 15, Point (d) of PERMA No. 5 of 2019 concerning the involvement of out-of-court institutions in providing assistance. This evidence proves that electronic assistance is not merely a technical solution but a valid innovation and instrument for providing substantive deliberation for judges in deciding cases. This innovation offers a new model for strengthening public services in the family law sector that is more inclusive and accessible without compromising the quality of the child's readiness assessment